Histamine-2 Receptor Antagonist for Gastric Bleeding Prophylaxis in Low-Risk Critically Ill Children: A Randomized Trial of Ranitidine - Sylvetri Lestari; Mayetti; Yusri Dianne Jurnalis; Eva Chundrayetti; Rusdi; Rahmi Lestari; Rinang Mariko (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The utility of stress ulcer prophylaxis (SUP) in critically ill children is a subject of ongoing debate, particularly in patients who do not present with classic high-risk features for stress-related mucosal disease (SRMD). This study aimed to evaluate the efficacy of ranitidine for preventing gastric bleeding in a heterogeneous cohort of critically ill children. Methods: A single-center, prospective, open-label, randomized controlled trial was conducted in a tertiary Pediatric Intensive Care Unit (PICU) in Indonesia. Children aged 1 month to 18 years admitted to the PICU were randomized to receive either intravenous ranitidine (1 mg/kg/dose twice daily) or standard care without prophylaxis for five days. The primary outcome was the incidence of overt gastric bleeding. Post-hoc power analysis and multivariable logistic regression were performed to contextualize the findings. Results: From 243 patients screened, 60 were randomized (30 per group). The cohort was predominantly composed of infants (60.0%) with respiratory distress. Overt gastric bleeding occurred in 1 of 30 patients (3.3%) in the ranitidine group versus 3 of 30 patients (10.0%) in the control group. This difference was not statistically significant (Relative Risk [RR] 0.33; 95% CI 0.04–3.11; p=0.612). After adjusting for a baseline imbalance in age, the odds of bleeding remained non-significantly lower in the ranitidine group (Adjusted Odds Ratio [aOR] 0.29; 95% CI 0.03–3.20). The study was found to be severely underpowered (16% power), and none of the bleeding events were clinically significant. Conclusion: In this small, underpowered trial of predominantly low-risk critically ill children, ranitidine did not significantly reduce the incidence of overt gastric bleeding. These findings, while limited by significant methodological weaknesses, do not support the routine use of SUP in similar pediatric populations and underscore the critical need for larger, more definitive trials to inform evidence-based risk-stratification strategies.